Evaluasi lanskap taman kota alun-alun Kapuas - Kartini, Kartini; Ruliyansyah, Agus; Arifin, Nur (Jurnal Arsitektur Lansekap, 2018)
Landcape evaluation of alun-alun Kapuas City park. Kapuas city park is a Green Open Space (RTH) that has aesthetic, ecological, social and economic functions. The condition of the park recently has the potential to differ from the previous design. The purpose of this research is to evaluate the condition of Alun-Alun Kapuas city park including theme, plants’ condition, and community perception. The method used in this research is: survey, interview and questionnaire. Data analysis using quantitative approach that descriptively interpreted. The results showed that the concept of repetition and suppressor in good condition, but it is imbalance. For the plants’ condition, it is divided into three condition: good condition 81,13%, average condition 9,43%, and bad condition 9.43%. Community perception about Kapuas City Park is 54% rate for average condition, 56% rate good for the park quality. Kapuas City Park is recently in a good, average, and bad condition. The good and average conditions can be maintained by giving information, making bulletin boards, hedges and signage. The bad condition can be improved by replanting to keep the theme on the park so the Kapuas City Park can be functioned properly.